2015
DOI: 10.1631/jzus.b1500098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipopolysaccharide on the hemocyte apoptosis of Eriocheir sinensis

Abstract: Abstract:In the present study, we investigated the possible toxicity mechanism of lipopolysaccharide (LPS) extracted from Gram-negative bacteria in Eriocheir sinensis hemocytes. Apoptotic hemocytes and reactive oxygen species (ROS) production induced by the LPS were monitored by the combination of flow cytometry and microscope observation. It was shown that LPS induced serious damage on the DNA and morphological changes in hemocytes, including cell shrinkage, fracture of nucleus membrane, margination, condensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…( 25 ) were due to size, reproductive period, or sampling season. In agreement with previous studies ( 31 , 32 ), two immune stimulation types led to a decrease in the THC, but no significant difference in the THC was found between genders. Similarly, Cheng et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…( 25 ) were due to size, reproductive period, or sampling season. In agreement with previous studies ( 31 , 32 ), two immune stimulation types led to a decrease in the THC, but no significant difference in the THC was found between genders. Similarly, Cheng et al.…”
Section: Discussionsupporting
confidence: 93%
“…It is likely the differences in the total number of hemocytes seen in the present study and that by Li et al (25) were due to size, reproductive period, or sampling season. In agreement with previous studies (31,32), two immune stimulation types led to a decrease in the THC, but no significant difference in the THC was found between genders. Similarly, Cheng et al ( 33) also reported no significant difference in the THC between genders of Macrobrachium rosenbergii, and Duchemin et al (5) observed that THC did not differ with gender in triploid or diploid C. gigas.…”
Section: Discussionsupporting
confidence: 92%
“…ROS production, induced by phagocytosis in the process of elimination 61 , is regarded as an important mechanism for microbicidal capacities 62 . ROS is usually used to determine immunity in marine invertebrates, such as bivalves 48,63 and crustaceans 43,64 . When hemocytes were stimulated (like exposure in vitro ), respiratory burst occurred and toxic reactive oxygen species were released 65,66 .…”
Section: Discussionmentioning
confidence: 99%
“…Untreated cells served as negative controls. Red fluorescence was detected using a BD Accuri C6 flow cytometer (BD Biosciences, San Jose, USA) (Hahm et al, 2014;Xu et al, 2015).…”
Section: Ros Measurementmentioning
confidence: 99%